ERCP-guided cholangioscopy using a single-use system: nationwide register-based study of its use in clinical practice - Lübbe, Jeanne; Arnelo, Urban; Lundell, Lars; Swahn, Fredrik; Törnqvist, Björn; Jonas, Eduard; Löhr, J.-Matthias; Enochsson, Lars (Endoscopy, 2015)
Background and study aims: Single-operator peroral cholangioscopy enables direct visualization of duct lesions, biopsy, and therapeutic interventions in the biliary and pancreatic ductal systems. The aim of this study was to address the use and outcome of this technology in wider clinical practice.Patients and methods: A nationwide study of endoscopic retrograde cholangiopancreatography (ERCP) procedures, with or without cholangioscopy, was conducted. Procedures that were registered in the Swedish Registry for Gallstone Surgery and ERCP (GallRiks), between 2007 and 2012 were included. The primary outcome was ERCP-specific adverse events.Results: Data from 36 352 ERCP procedures were analyzed, including 408 cholangioscopy procedures. Postprocedural adverse events were more prevalent when cholangioscopy was used (19.1 % vs. 14.0 %). Pancreatitis (7.4 % vs. 3.9 %) and cholangitis (4.4 % vs. 2.7 %) were ERCP-specific adverse events that were elevated in the cholangioscopy group. However, in multivariate analysis, the risks of intraprocedural and postprocedural adverse events were significantly increased in the cholangioscopy group whereas the risks of pancreatitis and cholangitis, when adjusted for confounders, were not. Conclusion: The single-operator peroral cholangioscopy technique is an advanced technique for intraluminal visual inspection, and for therapeutic intervention of the biliary and pancreatic ducts. However, there is a significantly increased risk of intra- and postprocedural adverse events. Thus, this method should preferably be performed at tertiary referral centers in carefully selected patients.